2018
DOI: 10.1016/j.mfglet.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Burr reduction mechanism in vibration-assisted micro milling

Abstract: This paper investigates the effect of vibration applied in feed direction on the burr generation mechanism in vibration-assisted micro milling. Kinematic analysis and finite element simulation are conducted for micro slot milling. Due to the vibration assistance in the feed direction, up milling and down milling takes place periodically on both of the cutting-in and cutting-out sides. This results in a reduction of burr formation. The results from both simulation and experiment confirm that the size of the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…between nominal and measured value was found for the characteristics angles (Table 1). The force signal compensation [19] was applied to remove the dynamic contribution of the sensor resonance. The frequency response functions (FRF) of the dynamometer were recognized from impact tests applied on the force directions as detailed in [33].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…between nominal and measured value was found for the characteristics angles (Table 1). The force signal compensation [19] was applied to remove the dynamic contribution of the sensor resonance. The frequency response functions (FRF) of the dynamometer were recognized from impact tests applied on the force directions as detailed in [33].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Different studies classified burrs formation according to its location in milling process namely as; entrance burr, exit burr, side burr, top burr and bottom burr [17] [18]. Micro milling FEM simulations were conducted for controlling the burr formation by vibration-assisted machining on the top burr generation results [19]. The 3D FE simulation was used to investigate the prediction capability of the model on different types of burr formation in micro ball milling of Ti-6Al-4V alloy [17].…”
Section: Introductionmentioning
confidence: 99%
“…The hardness of the hardened subsurface layer (average 3.98 GPa) from vibration-assisted machining is 16% lower than that of conventional machining [86]. The control of burr formation in micro milling was investigated by Chen et al [23]. They found that due to the vibration assistance in the feed direction, up milling and down milling take place periodically on both of the cutting-in and cutting-out sides.…”
Section: End Millingmentioning
confidence: 99%
“…That is the well-known size effects. Up to date, two issues which limit the further development of micro milling [22,23] should be urgently solved. Firstly, the deformation and vibration between micro cutter and workpiece would interfere the machining accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation